2010
DOI: 10.1111/j.1099-1123.2009.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Financial Reporting System: Can Audit Committees Deliver?

Abstract: This paper reviews the literature on audit committees in order to evaluate the extent to which committees are effective in terms of strengthening financial reporting. The paper aims to achieve two goals: first. to provide updated information about the effectiveness of the audit committee, and second to identify research opportunities. Compared with other reviews on the matter, we cover a broader spectrum of theoretical perspectives from various fields, methods, and countries. In particular, our review investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
358
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(387 citation statements)
references
References 145 publications
(279 reference statements)
13
358
0
16
Order By: Relevance
“…In a review of studies of the relationship between audit committee characteristics and audit committee effectiveness, Bédard & Gendron (2010) conclude that audit committee existence, members' independence and members' competence all influence effectiveness positively, whereas the number of meetings and the size of the committee have no significant impact. They lament the lack of research conducted outside the US, calling for research into the dynamics of audit committee processes.…”
Section: Audit Committee Processes Researchmentioning
confidence: 99%
“…In a review of studies of the relationship between audit committee characteristics and audit committee effectiveness, Bédard & Gendron (2010) conclude that audit committee existence, members' independence and members' competence all influence effectiveness positively, whereas the number of meetings and the size of the committee have no significant impact. They lament the lack of research conducted outside the US, calling for research into the dynamics of audit committee processes.…”
Section: Audit Committee Processes Researchmentioning
confidence: 99%
“…In Bahrain, the Bahrain CGC stated that, a majority of the AC should have the financial literacy qualifications. Financial expertise leads AC members to identify and ask knowledgeable questions that challenge management and external audit to a greater extent of financial reporting quality (Bédard and Gendron, 2010). It is generally agreed that the key duty of the AC is to review the financial reporting process to ensure the best quality of financial reports, thus the availability of an accounting and financial expertise in the AC would enhance its efficiency and its ability in detecting and preventing earnings management.…”
Section: Audit Committee Expertisementioning
confidence: 99%
“…Literature on AC has suggested that AC effectiveness essentially functions on AC characteristics (e. g. Persons, 2009;Bédard and Gendron, 2010;Dhaliwal et al, 2010;Li et al, 2012). Therefore, the perfect AC size with the right combination of skills and experience are critical in supporting the AC's ability in detecting and preventing earnings management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and size of boards of directors have been broadly investigated by scholars for their impact on enhancing the effectiveness of the boards' monitoring role and in mitigating the agency problem (Bedard, Chtourou & Courteau 2004;Bédard & Gendron 2010;Cheng & Warfield 2005;Cohen, J, Krishnamoorthy & Wright 2008;Davidson, Goodwin-Stewart & Kent 2005;Finnerty 1976;Jaffe 1974;Jensen 1993;Klein 2002b;Merchant & Rockness 1994;Xie, Davidson & DaDalt 2003). A board's effectiveness is also described as its ability to prevent managers from making decisions that conflict with stakeholder interests (Jo & Kim 2007).…”
Section: Board Structure (Principle 2) and Earnings Managementmentioning
confidence: 99%